Depression and blood pressure in high-risk children and adolescents: an investigation using two longitudinal cohorts. Issue 9 (25th September 2013) - Hammerton, Gemma; Harold, Gordon; Thapar, Anita; Thapar, Ajay
Abstract : Objective: To examine the relationship between blood pressure and depressive disorder in children and adolescents at high risk for depression. Design: Multisample longitudinal design including a prospective longitudinal three-wave high-risk study of offspring of parents with recurrent depression and an on-going birth cohort for replication. Setting: Community-based studies. Participants: High-risk sample includes 281 families where children were aged 9–17 years at baseline and 10–19 years at the final data point. Replication cohort includes 4830 families where children were aged 11–14 years at baseline and 14–17 years at follow-up and a high-risk subsample of 612 offspring with mothers that had reported recurrent depression. Main outcome measures: The new-onset of Diagnostic and Statistical Manual of Mental Disorder, fourth edition defined depressive disorder in the offspring using established research diagnostic assessments—the Child and Adolescent Psychiatric Assessment in the high-risk sample and the Development and Wellbeing Assessment in the replication sample. Results: Blood pressure was standardised for age and gender to create SD scores and child's weight was statistically controlled in all analyses. In the high-risk sample, lower systolic blood pressure at wave 1 significantly predicted new-onset depressive disorder in children (OR=0.65, 95% CI 0.44 to 0.96; p=0.029) but diastolic blood pressure did not. Depressive disorder at wave 1 did not predict systolic blood pressure at wave 3. A significant association between lower systolic blood pressure and future depression was also found in the replication cohort in the second subset of high-risk children whose mothers had experienced recurrent depression in the past. Conclusions: Lower systolic blood pressure predicts new-onset depressive disorder in the offspring of parents with depression. Further studies are needed to investigate how this association arises.